Eye-Movement Training Results in Changes in qEEG and NIH Stroke Scale in Subjects Suffering from Acute Middle Cerebral Artery Ischemic Stroke: A Randomized Control Trial - Carrick, Frederick Robert; Oggero, Elena; Pagnacco, Guido; Wright, Cameron H. G.; Machado, Calixto; Estrada, Genco; Pando, Alejandro; Cossio, Juan C.; Beltrán, Carlos (Frontiers in Neurology, 2016)
Context: Eye-movement training (EMT) can induce altered brain activation and change the functionality of saccades with changes of the brain in general. Objective: To determine if EMT would result in changes in qEEG and NIH Stroke Scales (NIHSS) in patients suffering from acute middle cerebral artery (MCA) infarction. Our hypothesis is that there would be positive changes in qEEG and NIHSS after EMT in patients suffering from acute MCA ischemic stroke. Design: Double blind randomized controlled trial. Setting and Participants: 34 subjects with acute MCA ischemic stroke at university affiliated hospital intensive care unit. Interventions: Subjects were randomized into a “control” group treated only with aspirin (125 mg/day) and a “treatment” group treated with aspirin (125 mg/day) and a subject specific EMT. Main Outcome measures: Delta-Alpha Ratio, Power Ratio Index and the Brain Symmetry Index calculated by quantitative electroencephalograms, and NIHSS. Results: There was strong statistical and substantive significant improvement in all outcome measures for the group of stroke patients undergoing EMT. Such improvement was not observed for the “control” group and there were no adverse effects. Conclusions: The addition of EMT to a MCA ischemic stroke treatment paradigm has demonstrated statistically significant changes in outcome measures and is a low cost, safe and effective complement to standard treatment.